2017
DOI: 10.1007/s00414-017-1667-6
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation based on aspartic acid racemization in dentine: what about caries-affected teeth?

Abstract: Age estimation based on aspartic acid racemization (AAR) in dentine is one of the most precise methods in adult age. Caries induces protein degradation and may have an impact on the kinetics of AAR in dentine. We systematically examined standardized prepared dentine samples from caries-affected teeth to clarify the question, if caries-affected teeth should not be used for age estimation based on AAR at all, or if the analysis of dentine samples from such teeth may be useful after removal of the caries-affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…The application of biochemical techniques, based on the natural process of aging, may provide a potential solution to this problem [ 12 ]. Until recently, the racemization of aspartic acid in dentin seemed to be the most accurate technique to determine the age of adult individuals [ 13 , 14 , 15 , 16 ]. However, epigenetics, the study of heritable changes in gene expression [ 17 , 18 ], has been shown to be a valuable and more accurate tool for age estimation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of biochemical techniques, based on the natural process of aging, may provide a potential solution to this problem [ 12 ]. Until recently, the racemization of aspartic acid in dentin seemed to be the most accurate technique to determine the age of adult individuals [ 13 , 14 , 15 , 16 ]. However, epigenetics, the study of heritable changes in gene expression [ 17 , 18 ], has been shown to be a valuable and more accurate tool for age estimation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of caries in teeth has been shown to influence the rate of racemization (Griffin et al 2008). Deviations up to 20.39 years were noted in carious teeth (Sirin et al 2018). It is assumed that caries induce protein degradation, which thereby generates small fragments of lower steric hints, leading to faster accumulation of d-aspartic acid (Collins et al 1999).…”
Section: Aspartic Acid Racemization (Aar)mentioning
confidence: 99%
“…Diesbezüglich am robustesten ist die Akkumulation von D-Asp, die spontan (nichtenzymatisch) bei einer biologisch eng einregulierten Körpertemperatur um 37°C abläuft. In kariös verändertem Dentin sowie in komplexeren Geweben als Dentin kann es allerdings im Rahmen der (erkrankungs-oder altersbedingten) Gewebsdegeneration zu Einflüssen auf die Akkumulation von D-Asp kommen [16,49]. Die Akkumulation von Pen ist abhängig von der Kohlenhydratstoffwechsellage und kann jedenfalls theoretisch bei einem über lange Zeit schlecht eingestellten Diabetes mellitus beschleunigt sein, wobei dies offenbar nur in Fällen mit dauerhafter schlechter medikamentöser Einstellung von praktischer Bedeutung zu sein scheint [23,24,26].…”
Section: Verknüpfung Mehrerer Molekularer Uhren In Modellen Zur Alterunclassified